2012
DOI: 10.1007/s13361-012-0442-7
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Layer Matrix Sublimation with Vapor-Sorption Induced Co-Crystallization for Sensitive and Reproducible SAMDI-TOF MS Analysis of Protein Biosensors

Abstract: Coupling immunoassays on self-assembled monolayers (SAMs) to matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) provides improved assay selectivity compared with traditional photometric detection techniques. We show that thinlayer-transfer (TLT) of α-cyano-4-hydroxycinnaminic acid (CHCA) MALDI matrix via vacuum sublimation followed by organic solvent-based vapor-sorption induced co-crystallization (VIC) results in unique matrix/analyte co-crystallization tendencies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…15 The latter is able to probe different surfaces, which recently opened up new perspectives in the molecular identification of SAMs, 17 nanoparticles, 18 biosensors, 19 and biochips. 20 Actually, the combination of surface MALDI-MS and SAMs on gold evolved in a technique termed by Mrksich as SAMDI.…”
mentioning
confidence: 99%
“…15 The latter is able to probe different surfaces, which recently opened up new perspectives in the molecular identification of SAMs, 17 nanoparticles, 18 biosensors, 19 and biochips. 20 Actually, the combination of surface MALDI-MS and SAMs on gold evolved in a technique termed by Mrksich as SAMDI.…”
mentioning
confidence: 99%
“…Here, we studied the influence of MeCN content in analyte/matrix solutions on sensitive detection of peptides by MALDI‐MS. The solubility of CHCA is heavily dependent on the solvent, with the solubility ranging from 850 mg/mL in dimethylsulfoxide to 0.2 mg/mL in water . To investigate the influence of the MeCN content of CHCA solution on the detection sensitivity, we set the concentration at 0.1 mg/mL, which was well below the reported 0.2 mg/mL, in order to avoid unexpected recrystallization induced when mixing with analyte solution and when contacting with the surface of the target plate.…”
Section: Resultsmentioning
confidence: 99%
“…For MALDI‐TOF MS, sample/matrix application techniques and preparation conditions such as solvent, matrix amount and temperature significantly influence the sensitivity, and a variety of the techniques and conditions have been developed . The most widely used among the techniques is the dried‐droplet (Karas–Hillenkamp) method, which was the original sample application method described in the earliest publications about MALDI‐MS.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that traditional optical detection methods can be replaced by MS for the screening of protein or small molecule microarrays [17,18]. This can avoid false positive results and directly provides molecular information about the analytes.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%